Ecosystem traps and where to find them. Issue 11 (27th July 2018) - Bosch, Jan; Olsson, Helena Holmström
Abstract: Today, companies operate in business ecosystems where they collaborate, compete, share, and learn from others with benefits such as to present more attractive offerings and sharing innovation costs. With ecosystems being the new way of operating, the ability to strategically reposition oneself to increase or shift power balance is becoming key for competitive advantage. However, companies run into a number of traps when trying to realize strategical changes in their ecosystems. In this paper, we identify 5 traps that companies fall into. First, the "descriptive versus prescriptive trap" is when companies assume that current boundaries between partners are immutable. Second, the "assumptions trap" is when powerful ecosystem partners assume that they understand what others regard as value‐adding without validating their assumptions. Third, the "keeping it too simple trap" is when companies overlooks the effort required to align interests. Fourth, the "doing it all at once trap" is when companies disrupt an ecosystem assuming that all partners can change direction at the same time. Finally, the "planning trap" is when companies are unable to move forward without a complete plan. We provide empirical evidence for each trap, and we propose an ecosystem engagement process for how to avoid falling into these. Abstract : Key findings: Repositioning in the ecosystem is fraud with risks. We identify the key traps that companies fall into, as well as provide guidance on how to avoid them when transitioning from current to desired state by shifting power between ecosystem partners.